Eficacia de tecnologías de nutrición sobre el rendimiento del maíz blanco para consumo en fresco, en Rocafuerte-Manabí - Barreiro Zambrano, Sandra Milena (2021)
The objective of the research was to evaluate the efficacy of nutrition technologies on the yield of white corn for fresh consumption. The experiment was developed during the rainy season of 2020 in the town of El Cardón in Rocafuerte canton, Manabí. The treatments evaluated were T1: NPK fertilization, T2: NPK fertilization + bioregulator cocktail, T3: NPK fertilization + soil improver + bioregulator cocktail, T4: Complete fertilization + soil improver + bioregulator cocktail, and T5: Control treatment. The main variables recorded were commercial ear production and net economic benefit (USD ha-1). The results obtained showed that treatments T2, T3 and T4 reached the highest production of commercial cobs, with increases of 27, 31 and 27% in contrast to the control treatment, and 10, 15 and 12% in relation to the conventional treatment based on NPK. The highest net economic benefit was achieved with the T2 treatment, with 314 USD ha-1. The complementary foliar nutrition in the phenological phases VE, V6 and V10, is effective to increase the yield and profitability of the white corn crop for fresh consumption.